A worldwide survey on training provisions for psychiatric trainees in WPA member associations. (17th February 2020) - Ng, Roger M. K.; Hermans, Marc H. M.; Belfort, Edgard; Bhugra, Dinesh
Abstract: This World Psychiatric Association (WPA) global survey of its WPA member society presidents using an online self-administered 15-item questionnaire successfully recruited 47 WPA member countries or regions (response rate = 39.8%) to provide responses about training provisions of psychiatric education at undergraduate, postgraduate, and post-qualified levels in their respective countries. There were significantly fewer responses from the low and middle income countries (LMIC) than the high income countries (HIC). At undergraduate level, the median duration of psychiatric education during medical school education was 4.0%. However, the current allocated time for psychiatric education was only around one-third to one-half of the time considered as optimal by the member countries or regions (optimal mean = 8.9%; optimal median = 10%). At the postgraduate level, the duration of training varied widely from 12–72 months, with a mean duration of 48 months. In 31% of the respondent countries, psychiatrists only required 36 or fewer months of post-graduate training. The number of months of training required for training a psychiatrist was significantly fewer in the LMIC than HIC. At post-qualified continuing medical education level, all respondents reported providing post-qualified continuing medical education. With the advent of internet technology, many respondents prefer having online training.